“The administrations that keep the Nation stagnant in its state of backwardness”: Regional press support for the Third Government of Ramón Castilla as resistance to local authority (1855-1860) - Gil Ichillumpa, Rubén (2024)
Outside of Lima, support for the central government, focused on Ramón Castilla and the constitutions of 1839 and 1856, was used as a tool to confront the abuses of power by local administrations. This was evidenced in numerous articles in the regional press, where attacks on press freedom and even personal attacks were highlighted and denounced as part of the arbitrariness of the prefects, their inefficiency, and their failure to follow the ideals of the government.